Isotopic analysis of atmospheric particulate from polar regions - BERTINETTI, STEFANO (Università degli studi di Genova, 2022)
A complete description of the origin, transport, fate, and effects of the atmospheric particulate matter (PM) in the polar regions is not yet available. Pb is a toxic element that is introduced into the environment in large amounts by anthropic activities, but it is also a useful atmospheric tracer because its isotopic composition is closely related to its geographic origin. Therefore, Pb isotopic analysis of PM10 collected from East Antarctica (Dome C, East Antarctic Plateau) and the Arctic (Svalbard Islands) has been performed, for sources recognition of the atmospheric Pb that reaches these remote areas. PM10 was directly collected from the atmosphere by air filtration upon PTFE membrane filters. In Antarctica, snow samples were collected from snow pits to evaluate the temporal variation of PM (provenience, composition) during the last decades. The information about the provenience of Pb was compared with that obtained from the atmospheric circulation models (back-trajectory analysis), allowing an overview of the long-range atmospheric transport of PM10 toward the Arctic and Antarctica. However, a better interpretation of the actual situation is only possible by considering different types of tracers, such as the isotopic composition of Sr, linked to the mineral dust input, and the elemental characterization of the PM10. Therefore, new methods for the elemental analysis of snow by ICP-AES, and the direct Sr isotopic analysis by ICP-MS/MS have been developed. These methods will be applied to the snow and PM10 samples which are still collected from the same sites, to extend the existing data set, and from additional sampling sites to improve our knowledge of the spatial variability of PM transport and deposition.